2013
DOI: 10.1074/jbc.m113.453597
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Nucleotide Sugar Transport in Trypanosoma brucei Alters Surface Glycosylation

Abstract: Background: Nucleotide sugar transporters (NSTs) provide availability of nucleotide sugars for glycosylation in the lumen of the Golgi apparatus. Results: The substrate specificities of four Trypanosoma brucei NSTs were characterized, and inhibition of TbNST4 resulted in glycosylation defects. Conclusion: TbNST4 plays an essential role in biosynthesis of glycoproteins in T. brucei. Significance: To understand the roles of TbNST(s) in the growth and pathogenesis of T. brucei.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 78 publications
(96 reference statements)
0
13
0
Order By: Relevance
“…To identify UDP-GlcNAc transporters, we used a yeast complementation approach in which a Kluyveromyces lactis mutant deficient in the Golgi transport of UDP-GlcNAc was used [ 19 ]. This mutant has been used for the identification of UDP-GlcNAc transporters from canine cells [ 20 ], Caenorhabditis elegans [ 21 ] and T. brucei [ 13 ]. Complementation assays are based on the less intense binding of the GS-II lectin from Griffonia simplicifolia , which specifically recognizes terminal GlcNAc residues, to the mutant cell surface.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To identify UDP-GlcNAc transporters, we used a yeast complementation approach in which a Kluyveromyces lactis mutant deficient in the Golgi transport of UDP-GlcNAc was used [ 19 ]. This mutant has been used for the identification of UDP-GlcNAc transporters from canine cells [ 20 ], Caenorhabditis elegans [ 21 ] and T. brucei [ 13 ]. Complementation assays are based on the less intense binding of the GS-II lectin from Griffonia simplicifolia , which specifically recognizes terminal GlcNAc residues, to the mutant cell surface.…”
Section: Resultsmentioning
confidence: 99%
“…In parasitic protozoa, the role of NSTs has been investigated in Leishmania spp. [ 11 , 12 ], T. brucei [ 13 ] and Toxoplasma gondi [ 14 ]. In L. major , knockout of the GDP-mannose (GDP-Man) transporter LPG2 resulted in mutants deficient in cell-surface phosphoglycan molecules displaying attenuated virulence in mice [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies that showed the occurrence of nucleotide sugar transporters in protozoan parasites established additional new concepts. In collaboration with John Samuelson's group, Luis Bredeston of my lab found endoplasmic reticulum and Golgi apparatus functions in these organisms (25), and in collaboration with Jay Bangs and Barbara Burleigh's groups, Li Liu and Yu Xin Xu of my lab described a nucleotide sugar transporter that transports both purine and pyrimidine substrates in Trypanosoma brucei, something we had never seen in any organism before (26). Together with John Boothroyd's group, Carolina Caffaro showed that a deletion of a transporter gene in Toxoplasma gondii contributed to changes in infectivity (27).…”
Section: Boston Mamentioning
confidence: 99%
“…Ammonium plays an active part in the regulation of the pH of acidic intracellular compartments of CHO expressing recombinant immunoadhesin tumor necrosis factor-IgG (TNFR-IgG), including trans-Golgi and it affects intracellular nucleotide sugar pools, especially UDP-N-acetylglucosamine (UDP-GlcNAc) and UDP-N-acetylgalactosamine 237 . The availability of nucleotide sugars in the lumen of the Golgi apparatus also depends on the transport, as shown in Trypanosoma brucei, where the inhibition of transporters modified surface glycosylation 286 . Increasing levels of glycosylation precursors, as result of cell culture medium supplementation for instance, alters the glycan distribution 124 .…”
Section: Introductionmentioning
confidence: 99%